Prying Open the Black Box of Causality: A Causal Mediation Analysis Test of Procedural Justice Policing - Pósch, Krisztián (Journal of quantitative criminology, 2021)
Review causal mediation analysis as a method for estimating and assessing direct and indirect effects. Re-examine a field experiment with an apparent implementation failure. Test procedural justice theory by examining to which extent procedural justice mediates the impact of contact with the police on police legitimacy and social identity.